FORMAREA PROFESORULUI-MUZICIAN PENTRU INSTRUIREA COPIILOR SUPRADOTAŢI - USM ADMIN (Moldova State University, 2007)
The present material is a presentation of some essential positions of the Concept for the university's formation of the teacher of musical education which is competent in education of gifted/talented children. The Concept's elements related in this article are called to show the most important objectives of professional training of the future teacher for gifted pupils including: professional competences; personal characteristics; basic attitudes.